2018
DOI: 10.1016/j.hrthm.2017.10.026
|View full text |Cite
|
Sign up to set email alerts
|

A novel algorithm increases the delivery of effective cardiac resynchronization therapy during atrial fibrillation: The CRTee randomized crossover trial

Abstract: In a cohort of CRT patients with a history of AF, eCRTAF significantly increased %eCRT pacing and %Vp during AF with a small increase in mean HR. This algorithm may represent a novel noninvasive method of significantly increasing effective CRT delivery during AF, potentially improving CRT response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…However, the performance CAFR has not been fully evaluated in a clinical study with patient outcomes. Medtronic has also developed an algorithm called effective CRT during AF that attempts to maximize effective CRT by increasing pacing rate based on analysis of the paced morphology of the unipolar LV electrogram (to distinguish LV capture from pseudo fusion) . Other device companies have similar triggered algorithms to maximize biventricular pacing…”
Section: Discussionmentioning
confidence: 99%
“…However, the performance CAFR has not been fully evaluated in a clinical study with patient outcomes. Medtronic has also developed an algorithm called effective CRT during AF that attempts to maximize effective CRT by increasing pacing rate based on analysis of the paced morphology of the unipolar LV electrogram (to distinguish LV capture from pseudo fusion) . Other device companies have similar triggered algorithms to maximize biventricular pacing…”
Section: Discussionmentioning
confidence: 99%
“…Twenty patients assigned to pharmacological treatment and 10 assigned to ablation and pacing had a heart failure event (heart failure related death, hospitalisation or worsening) which was statistically significant; quality of life also improved in the ablate and pace group (115). New algorithms may help deliver bi-ventricular pacing more effectively in patients with atrial fibrillation (183). However, CRT is more than just bi-ventricular pacing.…”
Section: Devices and Transplantation (700 Words)mentioning
confidence: 99%
“…It has been reported that in 50% of patients, a part of the measured biventricular pacing during programmed pacing is actually a fusion wave; this phenomenon is more obvious in patients with atrial fibrillation [44]. To solve this problem, a new algorithm has been developed; when the total capacity of fusion pacing exceeds a certain threshold, the pacemaker will automatically increase the pacing frequency appropriately [45]. Such a new algorithm for left ventricular fusion wave pacing may be useful in non-responders.…”
Section: Program Optimizationmentioning
confidence: 99%